Analysis of students' mathematical literacy ability in solving hots questions in view of learning style - Agustina, Marlita Dwi; Khotimah, Rita Pramujiyanti (Desimal: Jurnal Matematika, 2024)
Mathematical literacy is a person's ability to formulate, use and interpret mathematics. The purpose of the study in this article is to analyze students' mathematical literacy in solving HOTS questions about SPLDV materials based on students' learning styles. This type of research is qualitative ethnography. The subject of the study, eighth grade students of SMP Negeri 2 Karanganyar. Data collection techniques are observation, interview and documentation. Validity of data, triangulation of sources and methods. Data analysis techniques, flow methods. This research uses six basic skills of mathematical literacy, namely communication skills, mathematization, representation, determining problem-solving strategies, using operational language and symbols, formal language and technical language, as well as reasoning and giving reasons. The results of the study show that visual learning style students can use six basic mathematical literacy skills in solving HOTS questions in SPLDV, kinesthetic learning style students can use 5 basic mathematical literacy skills in solving HOTS questions in SPLDV. level, and students who have a kinesthetic learning style can use the 5 basic skills of mathematical literacy in solving SPLDV level HOTS questions.